Renewable Energy and Maluku's Natural Resources Strategies for Utilizing Local Potential for a Sustainable Future - Maryam Sangadji; Diah Wahyuningsih; Ummi Duwila; Desry Jonelda Louhenapessy (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the utilization of renewable energy in Maluku Province, emphasizing an integrative approach based on local potential. Maluku, as an archipelagic region, has diverse energy potential, including solar, geothermal, microhydro, wind, and biomass. However, the utilization rate of new and renewable energy (EBT) remains low due to infrastructure, regulatory, social capacity, and economic constraints. This study uses a qualitative descriptive method supported by data from interviews and secondary quantitative data from BPS, PLN, and the Ministry of Energy and Mineral Resources. The analysis was conducted through spatial-sectoral mapping, evaluation of actual obstacles, and formulation of SWOT-based strategies. The results show that almost all regencies/cities in Maluku have significant EBT potential, with suitable utilization in the household, fisheries, agriculture, and public service sectors. The main obstacles include limited interconnection networks, unsupportive investment regulations, low community technical capacity, and small market scale. The proposed strategy emphasizes community-based renewable energy development, integration with natural resource conservation, local community empowerment, and multi-stakeholder collaboration. This study emphasizes the importance of a just energy transition that is contextual to the characteristics of the archipelago.